ANALISIS AKUNTANSI PERSEDIAAN DAGANG BERDASARKAN PSAK No. 14 - Sa'adah, Lailatus; Mayasaroh, Siti; Murtiningtyas, Triana (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
The purpose of this research is to determine the suitability of the application of Accounting Standards regulated in PSAK No. 14 with the company. The type of research used in this research is comparative qualitative descriptive research with three stages, namely (a) interviews, (b) observations and (c) documents. The results of this research show that when recording inventory the company uses a perpetual system, meaning that every transaction that occurs is recorded in a journal. The inventory valuation method uses FIFO (First In First Out), which is a method of recording according to the goods entered first, then those goods will be used or issued or sold first. The company has presented inventory information in financial reports, namely in the balance sheet and profit and loss report, so it can be concluded that the implementation of inventory accounting in the company is in accordance with PSAK no. 14.